2015
DOI: 10.1177/0956797615573520
|View full text |Cite
|
Sign up to set email alerts
|

Modality and Morphology

Abstract: Written language is an evolutionarily recent human invention whose neural substrates cannot, therefore, be determined by the genetic code. How, then, does the brain incorporate skills of this type? One possibility is that written language is parasitic on evolutionarily older skills such as spoken language, while another is that dedicated substrates develop with expertise. If written language is parasitic on spoken language, then acquired deficits of spoken and written language should necessarily co-occur. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For example, VLSM can identify brain areas on a voxel-by-voxel basis that are critical for a given process, based on a continuous measure of impairment severity across a large sample, while case studies provide the opportunity to do more detailed testing and better characterize the nature of the processes subserved by these regions. The current study also complements smaller group studies that employ rigorously-matched experimental stimuli in order to tease apart the neural correlates of distinct subcomponents of reading or writing (Rapp et al, 2015). Also complementary, functional imaging studies in healthy individuals and acute stroke patients provide a snapshot of the larger network of regions recruited during a particular activity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, VLSM can identify brain areas on a voxel-by-voxel basis that are critical for a given process, based on a continuous measure of impairment severity across a large sample, while case studies provide the opportunity to do more detailed testing and better characterize the nature of the processes subserved by these regions. The current study also complements smaller group studies that employ rigorously-matched experimental stimuli in order to tease apart the neural correlates of distinct subcomponents of reading or writing (Rapp et al, 2015). Also complementary, functional imaging studies in healthy individuals and acute stroke patients provide a snapshot of the larger network of regions recruited during a particular activity.…”
Section: Discussionmentioning
confidence: 87%
“…In the modern era, much less attention has been dedicated to identifying the brain networks associated with writing (also referred to as spelling in the literature, depending on the task; Kemmerer, 2014; Lorch, 2013; Rapp and Dufor, 2011; Rapp et al, 2015; Starrfelt and Shallice, 2014). A recent meta-analysis of 11 functional imaging studies reported that the most consistent regions associated with writing were the left inferior temporal cortex, fusiform gyrus, inferior frontal cortex, and the posterior intraparietal sulcus (though not the angular gyrus, which has been frequently implicated in lesion studies; Purcell et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to consider the context and the manner in which cue words are presented. For instance, there are differences in lexico-grammatical patterns between spoken and written registers (Biber et al 2000;Rapp et al 2015), which can impact the responses.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…These four modalities share receptive and production areas of the brain, yet, they also have unique processing levels and neuroanatomical substrates (Berninger and Abbott 2010; Singleton and Shulman 2014). For instance, a person with a writing deficit may still speak normally, or vice versa (Rapp, Fischer-Baum, and Miozzo 2015). The locations of brain injuries are known to lead to different types of language deficits.…”
Section: Challengesmentioning
confidence: 99%